Preparing surgeons for the modern operating theatre: insights from a national survey on technology use and readiness - Roche, Adam F.; Burke, Eoghan; Kavanagh, Dara O.; Crimmins, Darach; Fleming, Christina A.; McInerney, Niall J.; O’Keeffe, Dara; Villanueva, Pablo Javier; Zilani, Gulam; Healy, Vincent; O’Brien, Donncha; McCloskey, Clare; et al. (Frontiers in Surgery, 2025)
IntroductionRapid advances in surgical technology require formal training in the use of devices and equipment, yet curricula rarely address technology, equipment, and consumables (TEC) proficiency in a systematic way. This study evaluated current TEC training practices, perceived needs, and barriers among consultant-level surgical educators in Ireland and used these findings to develop a national TEC Toolkit framework rooted in contemporary educational theory.MethodA national cross-specialty survey was distributed to consultant surgical educators, gathering quantitative ratings and qualitative insights regarding TEC education, barriers to readiness, and preferred educational strategies. The twenty-item survey was mapped to Kern's curriculum development framework and constructivist principles. Responses were analysed descriptively and thematically, and Kruskal–Wallis tests compared ratings across three specialty groupings.ResultsThirty-three of 39 educators responded (85%). Fifty-six percent reported having witnessed patient safety risks or workflow issues due to trainee unfamiliarity with TEC. A strong majority (over 90%) endorsed simulation-based training, hands-on workshops, and competency assessment as essential components of TEC education. Barriers included limited protected time, inconsistent access to TEC, and lack of curricular integration. Qualitative themes highlighted the need for practical skills development, multidisciplinary simulation, digital resources, and ongoing programme refinement. These priorities informed the proposed TEC Toolkit, which integrates simulation, multimedia modules, and structured assessment.ConclusionSurgical educators across Ireland overwhelmingly support structured, simulation-driven TEC training as an essential element of modern surgical safety. The proposed TEC Toolkit model offers a practical, evidence-based blueprint to improve TEC literacy and patient safety. Implementing and evaluating this toolkit will help to address current gaps and prepare trainees for the complexities of today's technology-rich operating theatres.